The Effect of Temperature on the Tribological Properties of Palm Kernel Activated Carbon-Epoxy Composite - Noor Ayuma Mat Tahir (Japanese Society of Tribologists, 2015)
The aim of this study was to investigate the effect of temperature on the tribological properties of Palm Kernel Activated Carbon-Epoxy (PKAC-E) composite. All specimens were formed into 10 mm diameter pins of 30 mm length, using a hot compaction technique. Tribological testing was carried out using a pin-on-disc tribometer in dry sliding conditions by applying temperatures in the range of 27°C to 150°C, at constant sliding speed, applied load, and sliding distance. The results showed that both coefficient of friction (COF) and wear rate of the composite increased with operating temperatures. Abrasive wear and crack formation that would induce delamination wear were identified as the predominant wear mechanisms.